Taxonomic studies on Zingiber (Zingiberaceae) in China VIII: Zingiber purpureum subsp. perdurans (Zingiberaceae: Zingiberoideae), a new subspecies from Yunnan, China - Bai, Lin; Ding, Hongbo; Li, Yong Liang (Phytotaxa, 2025)
Zingiber purpureum is a widely used medicinal plant. A new subspecies, Z. purpureum subsp. perdurans, which is distributed in southern Yunnan, is recognised here. It differs from the typical subspecies by the whole lower surface and midvein of upper surface of laminae, the whole ligules and leaf sheaths being covered by dense, long, erect, coarse hairs (leaves being generally glabrous except the mid-vein of lower surface of laminae and the margin of leaf sheaths and ligules in Z. purpureum sub. purpureum), and labella being broader (2.3–2.9 cm vs 1.7–2 cm) and more prominently winkled. This subspecies is also generally similar to Z. corallinum in its vegetative part, especially its rich indumentum and camphorous smell of rhizome, but Z. corallinum differs by having paler-coloured rhizome, broader laminae and longer ligules, longer spikes, smaller labella and lateral staminodes. The bracts are red in fruit for both species. However, when flowering the bracts of Z. corallinum are green, while the bracts of both subspecies of Z. purpureum are dark red to maroon, purplish or almost brown. Colour plates showing the diagnostic features, and information on its distribution, ecology and phenology of Z. purpureum subsp. perdurans are provided.